(y + z)³ ( i believe you were trying to do the expression to the power of 3)
(y + z)³ = (y + z)(y + z)(y + z)
Use the FOIL method:
(y + z)(y + z) = y² + yz + yz + z²
Simplify
y² + 2yz + z²
plug in the answer gotten back into the expression
(y² + 2yz + z²)(y + z)
FOIL again, distribute each number to the other.
y²(y) = y³
y(2yz) = 2y²z
y(z²) = yz²
y²(z) = y²z
2yz(z) = 2yz²
z(z²) = z³
2y²z + 2yz² + y³ + z³ + y²z + yz²
Simplify: add all like variables
2y²z + y²z = 3y²z
2yz² + yz² = 3yz²
3y²z + 3yz² + y³ + z³ is your answer, or y^3 + 3y^2z + 3yz^2 + z^3
hope this helps